Health Optimization in Primary Schools: Instilling Handwashing Habits as a Proactive Step Towards a Healthy Learning Environment - Rospita Panjaitan; Ester Julinda Simarmata; Rosdiana Samosir (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
This community project aims to promote understanding and implementation of hand washing behaviors at State Elementary School 173622 Sipagabu. Involving students, instructors, parents and school personnel, this activity was held on January 14 2024, employing outreach strategies in the form of talks and seminars. Evaluation of the programs demonstrated a considerable increase in comprehension of correct handwashing practices and awareness of its advantages. The results of group discussions and active involvement in the workshop suggested that there was a good impact on the implementation of hand washing habits in daily life. Full support from the school played a vital part in the success of this activity. Implementation steps and follow-up plans include the development of working groups and expansion of activities to additional schools. The conclusion of this assignment demonstrates accomplishment in making positive change in the educational environment. The sense of cooperation and commitment to ensuring the continuation of this effort are valuable assets to involve new parties and broaden the good influence to a wider degree. This abstract demonstrates a real contribution to enhancing health and hygiene at State Elementary School 173622 Sipagabu, building a firm foundation for similar activities in the future.